Influence of film forming substrate on self-organized gradient structure of fluoroacrylate/polyurethane composite emulsion - XIN Hua; LIU Jian-fang; YANG Jiang-peng; ZHANG Hui; ZHAO Xing (Cailiao gongcheng, 2020)
Fluoroacrylate/polyurethane composite emulsion (FPAPU) were synthesized by miniemulsion polymerization. The effect of four kinds of materials with different surface properties (aluminum plate, stainless steel plate, PTFE plate and glass plate) on the self-organized gradient distribution structure of fluorine-containing components in FPAPU latex film was studied. The results show that the gradient structure is not obvious when the film is formed on aluminum and stainless steel plate respectively. The gradient structure is obvious when the film is formed on PTFE and glass substrate respectively. Especially for the film formed on the glass plate, the content of fluorinated component is increased from film-substrate (F-S) surface to film-air (F-A) surface, and the difference of both sides of the film is obvious. The surface free energy difference can reach 11.71 mN/m. The apparent stratification structure is formed from F-S surface to F-A surface, and F-A surface is relatively rough. The film formed on glass substrate has excellent hydrophobicity and oleophobicity, and the contact angle of water and oil (diiodomethane) on which can reach 121.6ånd 90.6°respectively.